Microsoft Teams in the Perspective of the Users - Nurus Sifa’ul Fuaddah; Mega Mulianing Maharani (Universitas Islam Sultan Agung, 2021)
This study is about to know the users’ perspective on Microsoft Teams. The users of this study are the students of a certain school in Semarang. They are the users of Microsoft Teams in the distance learning. Microsoft Teams is the school choice; therefore, the students’ perspective are the data of this study. The data are taken through distributing close ended questionnaire to one hundred and twenty students who are the samples of this study. The validation of the questionnaire content follows the validation which is designed by Simon & White (2011). While for the reliability, the alpha coefficient is used to check it. In twelve questions, there are ten statement items that are highly understandable and two statement things that are moderately understandable. The students’ perspective is that Microsoft Teams mediate their interaction and communication with their teachers. It is as the solution tool for their distant learning.